Micro‐Raman And Micro‐Stratigraphic Analysis Of The Painting Materials In The Rock‐Hewn Church Of The Forty Martyrs In Şahinefendi, Cappadocia (Turkey). (12th May 2015) - Pelosi, C.; Agresti, G.; Andaloro, M.; Baraldi, P.; Pogliani, P.; Santamaria, U.; La Russa, M. F.; Ruffolo, S. A.; Rovella, N.
Abstract : This paper presents the results of analyses carried out on the paintings on the rock‐hewn walls of the Forty Martyrs church at Şahinefendi in Cappadocia (a UNESCO World Heritage Site), a central region of Turkey, performed during conservation work from 2007 to 2012. The micro‐samples were investigated by spectroscopic, micro‐stratigraphic and scanning electron microscopy analysis in order to study the painting technique, the materials and the degradation products. The micro‐stratigraphic analysis showed a white, sometimes pinkish, plaster. Micro‐Raman analysis, performed on cross‐sections of the mortars, enabled the detection of calcite, gypsum, anhydrite and calcium oxalate. Scanning electron microscopy and energy‐dispersive spectroscopy revealed a similar composition among all investigated phases, aside from minor differences such as the presence of diatoms in the second and third phases and of biotite, lime lumps and plants fragments in the fourth one. Apart from traditional pigments of medieval wall paintings, micro‐Raman analysis revealed the presence of lead‐based compounds and jarosite.